The Potential Impact of Succeeding Crops on Soil Carbon Pools, Carbon Sequestration, Beneficial Microbes and Enzyme Activities under Intensive Sugarcane-based Cropping Systems - Ch. S. Ramalakshmi (Journal of the Indian Society of Soil Science, 2023)
Soil organic carbon (SOC) is an essential edaphic component that influences the establishment and growth of the soil biota. It is most widely used as a quality indicator in humid tropics. The impact of different succeeding crops of sugarcane on the functional microbes, soil enzyme activities and soil carbon storage in relation to different carbon pools from different sugarcane based cropping systems was investigated in a tropical Inceptisols of North Coastal Andhra Pradesh. The cropping systems included sugarcane-sugarcane, sugarcane-rice, sugarcane-pulse, sugarcane-oil seed. Research results revealed that highest range (1.05-1.34%) and mean values (1.29) of total carbon and total nitrogen (N) (0.121%) were observed in surface soils (0-15 cm) of sugarcane-sugarcane cropping system followed by sugarcane-oilseed, sugarcane-pulse and sugarcane–rice system. Lowest mean C:N ratio of 8.75 was observed in surface soils of sugarcane-rice system and highest of 14.93 was recorded in sub-surface (15-30 cm and 30-45 cm) soils of sugarcane-sugarcane system. Regarding different carbon pools, SOC and microbial biomass carbon was highest with sugarcane-oil seed, closely followed by sugarcane pulse, whereas lowest were recorded in sugarcane-sugarcane system. Our studies clearly revealed that the sugarcane-pulse, sugarcane–oilseed and sugarcane–rice systems recorded highest amount of active carbon pools coupled with high functional microbes and enzyme activity, though highest total carbon was recorded in sugarcane-sugarcane system. Such systems may not only have practical application value but also lead to higher yield capacity with sustained soil and crop productivity.